Respuestas

2012-03-26T19:51:46+02:00

buenas tardes.solucion:12x-3(4x-2)+2(3x+3)-4(1-x)=

                                  :12x-12x-6+6x+6-4+4x

                                  :12x-12x+6x+4x=+6-6+4
                                  :10x=4
                                  :x=4/10=2/5   x=2/5

 
-7y+4(2-2y)-3(4-3y)-(y+5)=                     4x+3y+{-5x-(x-2y)}+3(2x-y)+x=

                                                          4x+3y-5x+x+2y+6x-3y+x=

-7y+8-8y-12+9y-y5                                4x-5x+x+6x+x=7x
                                                           3y+2y-3y=2y

                                                            7x+2y

-7y-8y+9y-y=-8+12-5

-6y+9y=-13+12
3y=-1


y=-1/3